Kekerasan Struktural dalam Novel Siri’ Karya Asmayani Kusrini: Perspektif Teori Kekerasan Johan Galtung - Siti Anisya; Aslan Abidin; Suarni Syam Saguni (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. Structural violence in the novel Siri' by Asmayani Kusrini: the perspective of Johan Galtung's theory of violence. This research is descriptive qualitative. The data in this study are in the form of phrases, words or sentences that represent the structural violence contained in the novel Siri' by Asmayani Kusrini with an emphasis on Johan Galtung's theory of violence. The data source for this research is the novel Siri' by Asmayani Kusrini. The rise of cases of violence that occur in public makes this research important to do, that violence is not just physically injuring someone, but a form of violence that is more than that. Violence can also occur in a structure, both social, political, economic and so on. For this reason, the purpose of this research is to find out and understand what structural violence is experienced by the characters in the novel Siri' by Asmayani Kusrini based on the perspective of Johan Galtung's theory of violence. The results of this study indicate that there are two types of structural violence contained in the data sources analyzed, namely structural violence in the form of mediation violence and repressive violence. Mediation violence consists of four data quotations while repressive violence consists of three data quotations.Keywords: Structural Violence, Novel Siri', Johan Galtung